Restaging in gynaecological cancers - Ayhan, A.; Celik, H.; Coskun, F.; Baykal, C.; Salman, M.C.; Aksan, G. (My University, 2005)
Regardless of recent technical developments in the scientific arena, stage is still the most important prognostic factor in gynaecological cancers. Surgical staging is performed in all types of gynaecologic cancers except for cervical cancer. Adjuvant therapies that contribute to survival are planned in the light of information obtained from staging procedures. Therefore, necessary information for further therapeutic management should be revealed by the end of surgical staging. A staging surgery that is not completed for any reason will not only deprive the patient of necessary treatments, but can also cause administration of unnecessary adjuvant treatments. This is especially important, given the undesired effects and cost of both chemotherapy and radiotherapy. A particularly relevant case in point is tumours that look like early stage; this is because upstaging up to 30% has been reported in ovarian and endometrial cancers. As for vulvar cancer, clinical staging has been reported to lead to about 15% over-diagnosis in comparison to surgical staging. Thus, the first step in all gynaecological cancers, except cervical cancer, should be to perform surgical staging when possible and unveil all surgical-pathological prognostic factors in the light of data obtained. Accordingly, restaging surgery should be considered in all cases that had incomplete staging. However, care should be taken to evaluate the benefits to be reaped together with the operative morbidity risk associated with the restaging procedure. This will both ensure accurate planning of postoperative treatment and provide a universal standard of approaching cancer patients and their treatments.
Keywords: Borderline ovarian cancer; Endometrial cancer; Ovarian cancer; Restaging; Staging; Tubal cancer; Vulvar cancer